Maximising Neurosurgical Residency Training: Integrating Skill, Cognition, and Resilience - Makkina, Charan; Panicker, Tony Varghese; Gandham, Edmond Jonathan (Nepal Journal of Neuroscience, 2026)
Neurosurgical residency training is uniquely demanding, requiring mastery of technical skills, advanced cognitive decision-making, and emotional resilience. Contemporary training faces additional pressures from duty-hour regulations, rapid technological advancement, subspecialization, and increasing emphasis on trainee well-being. This perspective reviews the evolution of neurosurgical training from classical apprenticeship models to modern, competency-based paradigms incorporating simulation, structured feedback, mentorship, and global collaboration. We provide a vision for a residency that balances surgical skill acquisition with reflective practice, professional identity formation, and resilience, aiming to produce neurosurgeons who are technically proficient, intellectually mature, and sustainable in the long term.